2018
DOI: 10.1113/ep087283
|View full text |Cite
|
Sign up to set email alerts
|

Plasma ferritin concentration is positively associated with in vivo fatty acid mobilization and insulin resistance in obese women

Abstract: High rates of fatty acid (FA) mobilization from adipose tissue are associated with insulin resistance (IR) in obesity. In vitro evidence suggests that iron stimulates lipolysis in adipocytes, but whether iron is related to in vivo FA mobilization is unknown. We hypothesized that plasma ferritin concentration ([ferritin]), a marker of body iron stores, would be positively associated with FA mobilization. We measured [ferritin], the rate of appearance of FA in the systemic circulation (FA Ra; stable isotope dilu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 19 publications
0
9
0
1
Order By: Relevance
“…Leptin has shown to stimulate hepcidin, the main iron regulatory hormone, whereas associations between serum visfatin, an adipokine secreted mainly by visceral adipose tissue, and different iron metabolism parameters were observed in patients with obesity and T2DM . Recently, plasma ferritin concentration have been linked with in vivo fatty acid mobilization and IR in obese women . Iron stores reflected by serum ferritin may therefore play an important role in glucose metabolism disorders through their effects on lipid metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Leptin has shown to stimulate hepcidin, the main iron regulatory hormone, whereas associations between serum visfatin, an adipokine secreted mainly by visceral adipose tissue, and different iron metabolism parameters were observed in patients with obesity and T2DM . Recently, plasma ferritin concentration have been linked with in vivo fatty acid mobilization and IR in obese women . Iron stores reflected by serum ferritin may therefore play an important role in glucose metabolism disorders through their effects on lipid metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…But the negative correlation between LDL-C and ferritin is influenced by diabetes frailly. This may be due to the role of ferritin in lipoprotein lipase activity, as described by Ryan et al [41]. At the same time, type 2 diabetes is closely related to lipase activity [13].…”
Section: Discussionmentioning
confidence: 81%
“…In a recent meta-analysis, it has been shown that serum ferritin concentration is connected with fasting plasma glucose, serum insulin concentration (17), and plasma triglycerides (TG) level (18). Additionally, studies revealed that serum ferritin levels are connected with homeostasis model assessment of insulin resistance (HOMA-IR) in a non-diabetic population but not in patients with impaired glucose tolerance (19)(20)(21)(22). Therefore, serum ferritin has been proposed as an early marker of insulin resistance (21).…”
Section: Introductionmentioning
confidence: 99%